Die Zukunft der Aufklärung - Rüsen, Jörn; Lämmert, Eberhard; Glotz, Peter (Edition Suhrkamp, 1988)
J. Rüsen, E. Lämmert und P. Glotz (Hrsg.): "Die Zukunft der Aufklärung". Suhrkamp Verlag, Frankfurt/M. 1988, 242 Seiten, brosch., 14,- DM